2010
DOI: 10.1007/s10815-010-9502-8
|View full text |Cite
|
Sign up to set email alerts
|

Low follicular fluid IL-6 levels in IVF patients are associated with increased likelihood of clinical pregnancy

Abstract: Lower follicular fluid IL-6 levels in IVF patients are associated with increased likelihood of clinical pregnancy. We hypothesize that endometrial receptivity is a likely target for any deleterious influences of elevated IL-6 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 44 publications
0
32
1
3
Order By: Relevance
“…TNFa in FF has been proposed to be related with oocyte quality and IVF outcomes , which is consistent with our results. Previous work suggested that elevated levels of IL6 in FF may be detrimental to implantation (Altun et al 2011). However, we did not observe this relationship in our study.…”
Section: Discussioncontrasting
confidence: 98%
“…TNFa in FF has been proposed to be related with oocyte quality and IVF outcomes , which is consistent with our results. Previous work suggested that elevated levels of IL6 in FF may be detrimental to implantation (Altun et al 2011). However, we did not observe this relationship in our study.…”
Section: Discussioncontrasting
confidence: 98%
“…Reduced follicular fluid concentrations of some cytokines have been reported to be associated with successful IVF treatment cycles (Ostanin et al, 2007;Altun et al, 2011). It is possible that increased levels of some cytokines might impair the endometrial receptivity as no other differences were observed in either oocyte or follicular parameters.…”
Section: Serum (N=30) ->mentioning
confidence: 99%
“…It is possible that increased levels of some cytokines might impair the endometrial receptivity as no other differences were observed in either oocyte or follicular parameters. IL-6 levels tend to increase with age (Altun et al, 2011). On the other hand, positive associations with pregnancy rates have been described for the concentrations of a number of other interleukins as well as for TNF-␣ and G-CSF (Ostanin et al, 2007).…”
Section: Serum (N=30) ->mentioning
confidence: 99%
See 1 more Smart Citation
“…As cytokines are involved in the regulation of follicles and as the follicular fluid contains cytokine-producing immune cells [23], increased intrafollicular inflammatory cytokine concentrations might have an effect on follicular physiology, resulting in lower oocyte quality and thereby in reduced outcome of IVF therapies. This suggestion is clinically supported by Altun et al [24]. They have reported an increased likelihood for clinical pregnancies in patients with low intrafollicular IL-6 cytokine concentrations in women without endometriosis.…”
Section: Discussionmentioning
confidence: 53%